The mediating role of emotions in the relationship between experiential marketing and repurchase intention of energy drinks: a case of generation Y - Phiri, Neo Elsie Morwesi (My University, 2018)
Generation Y is emerging as an enormous force in the marketplace, with its growing spending power and its members’ unique spending patterns. This research employs the Mehrabian and Russell (1974) S-O-R model to study the impact of experiential marketing on emotions and behavioural intention of Generation Y consumers in the energy drinks category. More than half of the energy drinks market comprises the fickle and disloyal consumption-driven Generation Y consumers. Customers are repeatedly attracted towards a brand based on its sensory experience. Marketing to customers’ taste, smell, touch, sight and sound therefore contributes to creating powerful memories, thereby presenting real opportunities for marketers to develop repeat purchase behaviour. While there are numerous studies investigating the impact of experiential marketing in developed economies such as the USA, the UK, or Australia, there are limited studies on experiential marketing conducted in emerging economies such as Brazil, Russia, India, China and South Africa (BRICS). The study proposes a mediation model where customer emotions are hypothesised as a key mediator in the relationship between experiential marketing and consumer buying behaviour. Following a descriptive research design, self-administered questionnaires were distributed to a stratified random sample of 700 students from four Universities in Gauteng, South Africa, 689 of whom responded. Respondents were asked to answer questions about their perceptions of their favourite energy drink brand. For the hypotheses testing, a structural equation modelling approach was used, using AMOS software. Results confirm that experiential marketing positively influences emotions, which in turn, influences consumers’ behavioural intentions. The results also confirmed that taste was the strongest multisensory experience. The results provide an empirical demonstration of the effects of experiential marketing on emotions and the subsequent impact of emotions on behavioural intentions. The findings of this study reinforce the importance of understanding the impact of customers’ emotions on behavioural intentions while enabling managers to develop an experiential branding strategy.
A thesis submitted to the Faculty of Commerce, Law and Management in fulfilment of the requirements for the degree of Doctor of Philosophy (Marketing),University of the Witwatersrand, Johannesburg, 2018
Keywords: Generation Y--South Africa; Consumer behavior--South Africa; Brand name products--South Africa